Analisis Tantangan Dan Solusi Industri Layanan Teknologi Di Indonesia: Studi Kualitatif - Rolando, Benediktus; Mulyono, Herry (Journal of Trends Economics and Accounting Research, 2025)
The technology services industry is a strategic sector in global economic growth facing various complex challenges, from technology adaptation to cybersecurity. While research on technological innovation is abundant, there remains a gap in in-depth analysis of strategic solutions for challenges faced by technology companies in developing countries, particularly Indonesia. This study aims to analyse the main challenges in the technology services industry and offer innovative solutions through a systematic literature review with content analysis methodology. Data was obtained from the Scopus database through a systematic filtering process from 720 initial articles to 50 final articles based on strict inclusion and exclusion criteria. Articles were selected based on topic relevance, methodological quality, and contribution to understanding industry challenges and solutions within the 2019-2024 timeframe. The research identifies four key areas requiring attention: (1) investment in research and development to drive sustainable innovation, (2) human resource development through comprehensive training programs, (3) strengthening strategic collaboration among stakeholders, and (4) regulatory framework enhancement to support industry growth. This study recommends an integrated approach combining digital transformation, workforce competency improvement, and cross-sector collaboration to enhance competitiveness and sustainability in Indonesia's technology services industry.